Breastfeeding and Allergic Diseases: What's New? - Giulia Nuzzi; Maria Elisa Di Cicco; Diego Giampietro Peroni (MDPI AG, 2021)
Asthma and other allergic disorders, such as atopic dermatitis and food allergies, are common chronic health problems in childhood. The rapid rise in the prevalence of these conditions registered over the last few decades has stressed the need to identify the modifiable risk factors associated with the development of these diseases. Breast milk, recognized as the gold standard for healthy growth and development of the newborn, is one of the major factors associated with a lower incidence of allergic and infectious diseases in childhood and young adulthood. Although the underlying mechanisms for these effects are not well understood, breastfeeding leads to immune system maturation. In this narrative review, we summarize existing evidence on breastfeeding and human milk composition in relation to allergic disease prevention or development.